Quantitative 1H-NMR spectroscopy for hydrophilic components of Japanese horse mackerel Trachurus japonicus for quality evaluation - Ryuichi Watanabe; Kanako Hashimoto; Yuko Murata; Takashi Matsuda; Kenji Ishihara; Ryoji Matsushima; Toshiyuki Suzuki; Takeya Yoshioka (Fisheries Science, 2025)

Generation of canine gallbladder cholangiocyte organoids from healthy and gallbladder mucocele patient dogs for functional analysis of anion channels - Itsuma Nagao; Hirotaka Tomiyasu; Yuko Goto-Koshino; Kota Nakase; Takumi Tsuruta; Yuto Namiki; Ryuichiro Sato; Yu Takahashi; Yuko Hashimoto; Yosuke Takahashi; Naohiro Takahashi; James K. Chambers; et al. (The Veterinary Journal, 2025)

Nicotinamide N-methyltransferase enhances paclitaxel resistance in ovarian clear cell carcinoma - Ryoko Kikuchi-Koike; Masaru Sakamoto; Yuko Sasajima; Yuko Miyagawa; Hiroshi Uozaki; Kenji Umayahara; Kei Hashimoto; Yuko Takahashi; Kazuki Takasaki; Chikara Kihira; Haruka Nishida; Takayuki Ichinose; et al. (Human Cell, 2025)
Nicotinamide N-methyltransferase (NNMT) is an S-adenosyl-l-methionine (SAM)-dependent cytosolic enzyme, and a growing body of evidence suggest that it plays an essential role in cancer progression. Recently, NNMT has a role in methylation metabolism and tumorigenesis and was associated with a poor prognosis against numerous cancers. In addition, it has been reported that NNMT has been overexpressed in the stroma of advanced high-grade serous carcinoma and may contribute to decreased survival. This study aimed to identify novel biomarkers to predict resistance and investigate their clinicopathologic significance in paclitaxel-resistant advanced or recurrent ovarian clear cell carcinoma (OCCC). Fluorescence-labeled two-dimensional differential gel electrophoresis (2D-DIGE), immunohistochemical, and MASCOT analyses allowed us to identify the cytoplasmic metabolic enzyme NNMT. In cultured cell studies, NNMT protein expression was higher in paclitaxel-resistant OVMANA and OVTOKO cells than in paclitaxel-sensitive KK and ES-2 cells. Furthermore, although analysis of clinical tissue samples showed no association with poor prognosis in 7 individuals with low NNMT expression in the cytoplasm of OCCC cells, high expression of NNMT in the cytoplasm of OCCC cells may be associated with low sensitivity to paclitaxel in OCCC and may have prognostic implications. Therefore, targeting therapy to reduce cytoplasmic NNMT expression levels may increase the sensitivity of OCCC to paclitaxel.

Effects of different exercise intensities or durations on salivary IgA secretion - Takamasa Uchino; Masataka Uchida; Reita Ito; Shumpei Fujie; Keiko Iemitsu; Chihiro Kojima; Mariko Nakamura; Kazuhiro Shimizu; Yuko Tanimura; Yasushi Shinohara; Takeshi Hashimoto; Tadao Isaka; et al. (European Journal of Applied Physiology, 2024)
Purpose This study aimed to examine changes in salivary immunoglobulin A (s-IgA) secretion at different intensities or durations of acute exercise. Methods Twelve healthy untrained young males were included in randomized crossover trials in Experiment 1 (cycling exercise for 30 min at a work rate equivalent to 35%, 55%, and 75% maximal oxygen uptake [ $${\dot{\text{V}}}$$ V ˙ O 2max ]) and Experiment 2 (cycling exercise at 55% $${\dot{\text{V}}}$$ V ˙ O 2max intensity for 30, 60, and 90 min). Saliva samples were collected at baseline, immediately after, and 60 min after each exercise. Results Experiment 1: The percentage change in the s-IgA secretion rate in the 75% $${\dot{\text{V}}}$$ V ˙ O 2max trial was significantly lower than that in the 55% $${\dot{\text{V}}}$$ V ˙ O 2max trial immediately after exercise (− 45.7%). The percentage change in the salivary concentration of cortisol, an s-IgA regulating factor, immediately after exercise significantly increased compared to that at baseline in the 75% $${\dot{\text{V}}}$$ V ˙ O 2max trial (+ 107.6%). A significant negative correlation was observed between the percentage changes in saliva flow rate and salivary cortisol concentration (r = − 0.52, P < 0.01). Experiment 2: The percentage change in the s-IgA secretion rate in the 90-min trial was significantly lower than that in the 30-min trial immediately after exercise (−37.0%). However, the percentage change in salivary cortisol concentration remained the same. Conclusion Our findings suggest that a reduction in s-IgA secretion is induced by exercise intensity of greater than or equal to 75% $${\dot{\text{V}}}$$ V ˙ O 2max for 30 min or exercise duration of greater than or equal to 90 min at 55% $${\dot{\text{V}}}$$ V ˙ O 2max in healthy untrained young men.

Involvement of the vagus nerve and hepatic gene expression in serum adiponectin concentrations in mice - Naoto Hashimoto; Ryuji Nagata; Kyu-Ho Han; Manabu Wakagi; Yuko Ishikawa-Takano; Michihiro Fukushima (Journal of Physiology and Biochemistry, 2024)

Sublingual immunotherapy for 4 years increased the number of Foxp3+ Treg cells, which correlated with clinical effects - Tetsuya Terada; Masaya Matsuda; Miki Inaba; Junpei Hamaguchi; Naoki Takemoto; Yusuke Kikuoka; Yuko Inaka; Harumi Sakae; Kennosuke Hashimoto; Hayato Shimora; Kazuyuki Kitatani; Ryo Kawata; et al. (Inflammation Research, 2021)

Risk factors for 30-day mortality among patients with Stenotrophomonas maltophilia bacteraemia - Takehiro Hashimoto; Kosaku Komiya; Naoko Fujita; Yuko Usagawa; Mari Yamasue; Kenji Umeki; Masaru Ando; Shin-ichi Nureki; Kazufumi Hiramatsu; Jun-ichi Kadota (Infectious Diseases, 2020)

MPTP-induced dopaminergic neurotoxicity in mouse brain is attenuated after subsequent intranasal administration of (R)-ketamine: a role of TrkB signaling - Atsuhiro Fujita; Yuko Fujita; Yaoyu Pu; Lijia Chang; Kenji Hashimoto (Psychopharmacology, 2020)

Consumption of lycopene-rich tomatoes improved glucose homeostasis in rats via an increase in leptin levels - Naoto Hashimoto; Naoki Tominaga; Manabu Wakagi; Yuko Ishikawa-Takano (Journal of Natural Medicines, 2020)

Lack of deuterium isotope effects in the antidepressant effects of (R)-ketamine in a chronic social defeat stress model - Kai Zhang; Hidetoh Toki; Yuko Fujita; Min Ma; Lijia Chang; Youge Qu; Shingo Harada; Tetsuhiro Nemoto; Akiko Mizuno-Yasuhira; Jun-ichi Yamaguchi; Shigeyuki Chaki; Kenji Hashimoto (Psychopharmacology, 2018)

Gender differences in the effects of job insecurity on psychological distress in Japanese workers: a population-based panel study - Yuko Kachi; Hideki Hashimoto; Hisashi Eguchi (International Archives of Occupational and Environmental Health, 2018)

Alterations in amino acid levels in mouse brain regions after adjunctive treatment of brexpiprazole with fluoxetine: comparison with (R)-ketamine - Min Ma; Qian Ren; Yuko Fujita; Chun Yang; Chao Dong; Yuta Ohgi; Takashi Futamura; Kenji Hashimoto (Psychopharmacology, 2017)

Alterations in glutamatergic signaling in the brain of dopamine supersensitivity psychosis and non-supersensitivity psychosis model rats - Yasunori Oda; Yuko Fujita; Kengo Oishi; Yusuke Nakata; Masayuki Takase; Tomihisa Niitsu; Nobuhisa Kanahara; Yukihiko Shirayama; Kenji Hashimoto; Masaomi Iyo (Psychopharmacology, 2017)

7,8-Dihydroxyflavone, a TrkB agonist, attenuates behavioral abnormalities and neurotoxicity in mice after administration of methamphetamine - Qian Ren; Ji-Chun Zhang; Min Ma; Yuko Fujita; Jin Wu; Kenji Hashimoto (Psychopharmacology, 2014)

Protective effects of the antioxidant sulforaphane on behavioral changes and neurotoxicity in mice after the administration of methamphetamine - Hongxian Chen; Jin Wu; Jichun Zhang; Yuko Fujita; Tamaki Ishima; Masaomi Iyo; Kenji Hashimoto (Psychopharmacology, 2012)

Glycine and d-serine, but not d-cycloserine, attenuate prepulse inhibition deficits induced by NMDA receptor antagonist MK-801 - Nobuhisa Kanahara; Eiji Shimizu; Shintaro Ohgake; Yuko Fujita; Mami Kohno; Tasuku Hashimoto; Daisuke Matsuzawa; Yukihiko Shirayama; Kenji Hashimoto; Masaomi Iyo (Psychopharmacology, 2008)

Evolutionary relationships of deep-sea mussels inferred by mitochondrial DNA sequences - Hiromi Iwasaki; Akiko Kyuno; Mifue Shintaku; Yuko Fujita; Yoshihiro Fujiwara; Katsunori Fujikura; Jun Hashimoto; Leonardo de Oliveira Martins; Andrey Gebruk; Jun-Ichi Miyazaki (Marine Biology, 2006)

Abstract of Poster Presentation - Hiroshi Uchida; Tetsuo Maruyama; Jkuko Sugiura; Takashi Kajitani; Touru Arase; Masanori Ono; Takashi Nagashima; Hirotaka Masuda; Hironori Asada; Yasunori Yoshimura; Soichiro Saito; Mila Ghosh; et al. (Human Cell, 2005)

New Approach for the Establishment of an Hepatocyte Cell line Derived from Rat Early Embryonic Stem Cells - Isao Tabei; Hisashi Hashimoto; Isamu Ishiwata; Yuko Tokieda; Toshiaki Tachibana; Masakazu Akahori; Shigeya Kyouda; Hirotaka Kubo; Katsuhiko Yanaga; Yoji Yamazaki; Shin-ichiro Takahashi; Kahei Sato; et al. (Human Cell, 2003)

Establishment and Characterization of a Lymphoepithelial-like Carcinoma Cell Line (HUUCLEC) Derived from the Human Uterine Cervix. - Kazushige KIGUCHI; Isamu ISHIWATA; Yuko TOKIEDA; Megumi IGUCHI; Chieko ISHIWATA; Masanori IWATA; Bunpei ISHIZUKA; Hiroyuki YOSHIKAWA; Toshiaki TACHIBANA; Hisashi HASHIMOTO; Hiroshi ISHIKAWA (Human Cell, 2002)

Circadian and senescence-enhanced expression of a tobacco cysteine protease gene - Tadamasa Ueda; Shigemi Seo; Yuko Ohashi; Junji Hashimoto (Plant Molecular Biology, 2000)

Kinetic Analysis of Tetraethylammonium Transport in the Kidney Epithelial Cell Line, LLC-PK1 - Yoshiko Tomita; Yuko Otsuki; Yukiya Hashimoto; Ken-ichi Inui (Pharmaceutical Research, 1997)